Terorisme di Indonesia: Antara Kepentingan Politik Negara dan Permasalahan Ontologis - Pabyantara S.M., Dias; Wibowo, Prihandono; Zamzamy, Ahmad (Global and Policy Journal of International Relations, 2018)
The arguments on terrorism has been debated since long time, and yet ther has been no collective agreement of how to define terrorism. As a major Moslem country, Indonesia also has this problem, diversity of definitions. Here, terrorism is crossing path with religious and nationalism discourses. This writing is aimed to mapping the various definition of terrorism in both academia and government. This paper consist of three parts. First, explanation on how state‟s perspective on terrorism is always fluidly folow the political interest. Second, The academia definitions that has ontological precisition. The last students perception on terrorism that goes along with government‟s. Keywords: Terrorism, Definition, Indonesia, College StudentsHTTDOI : https://doi.org/10.33005/jgp.v6i02.1822